Open Source software development - just another case of collective invention? - Margit Osterloh; Sandra Rota (Center for Research in Economics, Management and the Arts (CREMA), 2005)
Does Open Source (OS) represent a new innovation model, and under what conditions can it be employed in other contexts? A look into history shows that OS isn't a unique example of what is called "collective invention". Other examples are blast furnaces in Britain's Cleveland district, steam engine design, and more recently, the flat panel display industry. While OS shares many similarities with these cases of collective invention, there is a main difference: Other collective invention regimes did not survive after the development of a dominant design. It is argued that two factors can explain the difference. Firstly, OS licenses are important institutional innovations that make OS survive as a common property. Secondly, the second order social dilemma, which arises when it comes to developing and enforcing OS licenses, is overcome by the existence of intrinsically motivated contributors. It is asked under which conditions this kind of motivation is developed and sustained. We argue that it is the existence of certain selfgovernance- mechanisms which OS licenses are a part of. We conclude that OS differentiates itself from other cases of collective invention by its success in solving the second order social dilemma of rule development and enforcement.
Keywords: 330; Open source software; collective invention; intrinsic motivation; copyleft; conditional cooperation